Forced migration as a deterrence strategy in civil conflict (2014)
The forced rural-urban migration in Colombia is a phenomenon that could be seen as the collateral damage of an armed conflict that takes place mainly in rural areas. Nevertheless, there is a significant percentage of cases in which the main reason to flee is a direct threat by an armed actor. This chapter proposes a possible reason why an illegal armed group displaces population from rural to urban areas.